Adult Diabetic Ketoacidosis: An Overview, Diagnosis, Treatment, Emergency, and Nursing Interventions - Alenazy, Souad Mohammad; Wahishi , Amna Mohammed; Albeshri , Nouf Omran; Al Baqal , Suaad Abdullah; Alabdulaziz, Wed Mohammed; Almutairi, Dlwl Rabeh; Alharbi, Muteb Fuhayd; Alshammari, Abdullah Batel; Al Somali, Rawdah Mohammed (Journal of Ecohumanism, 2024)
Background: Diabetic ketoacidosis (DKA) is a life-threatening complication commonly seen in individuals with diabetes, particularly those with type 1 diabetes mellitus (T1DM), although it also occurs in individuals with type 2 diabetes mellitus (T2DM). DKA is precipitated by factors such as infections, trauma, surgery, and non-compliance with insulin therapy. The condition is marked by hyperglycemia, metabolic acidosis, and ketonemia. Immediate management is crucial to prevent severe complications, including coma and death. Aim: This article aims to provide an overview of DKA, including its etiology, pathophysiology, diagnostic approaches, treatment strategies, and nursing interventions. Methods: A comprehensive review of the existing literature on DKA was conducted, focusing on the epidemiology, pathophysiology, diagnosis, and treatment modalities. The article examines clinical management approaches, including insulin therapy, fluid resuscitation, and electrolyte correction, alongside the role of nursing interventions in the acute care setting. Results: The incidence of DKA varies across regions, with a higher prevalence observed among individuals with T1DM and in urban populations with poor adherence to insulin therapy. Diagnostic criteria include elevated blood glucose levels, metabolic acidosis, and the presence of ketones. The management of DKA involves aggressive rehydration, insulin administration, and correction of electrolytes. Nursing interventions focus on monitoring vital signs, assessing for complications, and providing patient education to prevent recurrence. Conclusion: DKA is a preventable but serious complication of diabetes that requires prompt recognition and treatment. Healthcare professionals, particularly nurses, play a critical role in managing the acute phase of DKA and in educating patients to prevent future episodes. Enhanced awareness, early intervention, and improved adherence to treatment can significantly reduce morbidity and mortality associated with DKA.